Drosophila Innate Immunity Involves Multiple Signaling Pathways and Coordinated Communication Between Different Tissues - Yu, Shichao; Luo, Fangzhou; Xu, Yongyi; Zhang, Yan; Jin, Li Hua (Frontiers in Immunology, 2022)
The innate immune response provides the first line of defense against invading pathogens, and immune disorders cause a variety of diseases. The fruit fly Drosophila melanogaster employs multiple innate immune reactions to resist infection. First, epithelial tissues function as physical barriers to prevent pathogen invasion. In addition, macrophage-like plasmatocytes eliminate intruders through phagocytosis, and lamellocytes encapsulate large particles, such as wasp eggs, that cannot be phagocytosed. Regarding humoral immune responses, the fat body, equivalent to the mammalian liver, secretes antimicrobial peptides into hemolymph, killing bacteria and fungi. Drosophila has been shown to be a powerful in vivo model for studying the mechanism of innate immunity and host-pathogen interactions because Drosophila and higher organisms share conserved signaling pathways and factors. Moreover, the ease with which Drosophila genetic and physiological characteristics can be manipulated prevents interference by adaptive immunity. In this review, we discuss the signaling pathways activated in Drosophila innate immunity, namely, the Toll, Imd, JNK, JAK/STAT pathways, and other factors, as well as relevant regulatory networks. We also review the mechanisms by which different tissues, including hemocytes, the fat body, the lymph gland, muscles, the gut and the brain coordinate innate immune responses. Furthermore, the latest studies in this field are outlined in this review. In summary, understanding the mechanism underlying innate immunity orchestration in Drosophila will help us better study human innate immunity-related diseases.